Ferroelectric ceramics manufactured from nano-sized powders of bi-containing layer-structured phases. Issue 4 (15th June 2016) - Nesterov, A. A.; Topolov, V. Yu.; Panich, E. A.
ABSTRACT: Methods to improve dielectric and piezoelectric properties of ferroelectric ceramics with high Curie temperatures (TC > 700 K) are discussed. In the first method improving the electrophysical properties is achieved due to a change in technology of the synthesis of powders of ferroelectric phases, and a proposed technological mode enables one to keep a composition of these powders due to a decrease of temperature of the synthesis of the chemically active powders and to a decrease of temperature of sintering. In this method high-temperature ferroelectric ceramics based on the Aurivillius phases are characterised by the piezoelectric coefficient d33 ≤ 40 pС / N and dielectric permittivity ϵ T 33 /ϵ0 ≤ 230. The second method is concerned with ferroelectric phases of PbTiO3   – PbZrO3   – Bi4 Ti3 О12   – МеТiO3  (Ме = Са, Sr, Ва), and on this basis ceramics are formed with larger piezoelectric parameters and TC > 700 K. Temperature of the synthesis of powders based on ferroelectric phases, obtained using the low-temperature method, is lower by 430 K on the average, at reducing the process time range by more than 3 times.